How firms grow: clustering as a dynamic model of internationalization - Maitland, Elizabeth; Rose, Elizabeth L; Nicholas, Stephen (Journal of International Business Studies, 2005)
This paper provides a methodology for identifying the dynamics of international firm expansion, demonstrating systematic evidence of both ‘toe in the water’ and concentrated bursts of internationalization by US multinational enterprises. We use the methodology of statistical process control to analyze initial investments in host countries and develop a numerical measure of temporal clustering or bunching. Using this measure, we identify two distinct patterns of growth; whereas some firms cluster their investments over time, others do not cluster their investments. For firms that cluster, three types of clustering strategy are identified: concentrating, hibernating, and hybrid. Arguments based on internal firm architecture, experience, and learning are advanced to explain these findings.